Character Education: Cultivating Students' Religious Character Based on Madrasah Culture - Rohman, Nurur; Ammathul Firdhausyah, Ananda; Jannah, Raudlatul; Putri, Candra Avista (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
Character cultivation is a critical component of educational systems worldwide. Character education needs to be instilled through curriculum frameworks that align with national educational goals by developing cultural values and national character. This research aims to describe and analyze the cultivation of students' religious character, identify supporting factors, and examine inhibiting factors in the cultivation of students' religious character through madrasah culture at an Islamic elementary school in Lamongan, East Java. This qualitative research collected data through observation, documentation, and interviews. The analysis employed the Miles and Huberman model, including data reduction, data presentation, and verification/conclusion drawing. The research findings reveal that the cultivation of religious character in students based on madrasah culture is implemented through planning aspects, implementation (physical artifact layer, non-physical artifact layer or behavior, and verbal artifact layer or values and beliefs), and evaluation. Supporting factors in instilling religious character in students based on madrasah culture include supportive facilities and cooperation from the school community. The inhibiting factors in cultivating religious character in students based on madrasah culture are students' different family backgrounds and lack of parental support